PENGARUH INSENTIF DAN IKLIM ORGANISASI SEKOLAH TERHADAP MOTIVASI KERJA GURU TAMAN KANAK-KANAK KECAMATAN AKABILURU KABUPATEN LIMA PULUH KOTA - -, Risnawati (Menara Ilmu, 2018)
This research aims to examine and analyze the effect of incentive and school organizationclimate toward working motivation of kindergarten teacher. The hypothesis in this researchare; 1) incentive has significant effect toward working motivation of kindergarten teacher, 2)organization climate has significant effect toward working motivation of kindergarten teacher,3) incentive and organization climate have significant effect toward working motivation ofteacher.The sample of this research are 73 kindergarten teachers. To examine the relation andinfluence of dependent and independent variables, the date is analyzed by using softwareSPSS.The result of this research shows that giving incentive for kindergarten teacher has significanteffect toward working motivation of kindergarten teacher. It can be seen that workingmotivation of kindergarten teacher in Akabiluru is better. The organization climate hassignificant effect toward working motivation of teacher. And simultaneously, giving incentiveand organization climate affect working motivation of kindergarten teacher.This discovery supports Herzberg’s theories. And this discovery also give understanding aboutthe important role of incentive and school organization climate toward working motivation ofkindergarten teacher.Keywords : incentive, organization climate, motivation